Efek Air Perasan Umbi Bawang Merah (Allium ascalonicum L.) terhadap Profil Lipid Plasma Mencit (Mus musculus) - Ismawati Ismawati; Sri Wahyuni; Nora Wirna (Fakultas Kedokteran Universitas Riau, 2010)
One of atherosclerosis risk factor is dislipidemia. One of plant that is expected to overcome dislipidemia is shallot(Allium ascalonicum L.). The aim of this research was to know the effect of shallot’s extraction water on the plasmalipid profile of mice. Groups with treatment consist of yolks group, and shallot water extraction divided into threetreatmen level ; 20%, 40% and 80%. Parameters that were measured were total cholesterol level, LDL, HDL andplasma triglyceride of mice in the end of treatment. Simvastatin and aquadest were separately used as positive andnegative control. This research proves that shallot’s extortion water has effect in decreasing the level of total cholesterol,LDL and triglyceride and also has effect in increasing level of HDL plasma with 80% of concentration as the bestconcentration.